The Irish revival a complex vision - Valente, Joseph 1958-; Howes, Marjorie 1962- (Syracuse University Press, 2023)
The Irish Revival has inspired a richly diverse and illuminating body of scholarship that has enlarged our understanding of the movement and its influence. Here, the contributors seeks to reimagine the field by interpreting the Revival through the concept of complexity , a theory recently developed in the information and biological sciences